Validasi Dimensi-Dimensi pada Skala Pembelajaran Aktif di SMP berdasarkan Pandangan Guru Indonesia - Y Yulianti; Laurens Kaluge (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
ABSTRACT This was a preliminary study to explore the constructs on active instruction as perceived by Indonesian teachers at junior secondary schools in order having an appropriate measure for teaching. Secondary data, picked up from MGPBE under the sponsorship of European Union, were used. There were two steps of sampling process. Firstly, picking up by chance 917 participating teachers originated from seven provinces such as East Nusatenggara, West Nusatenggara, Central Java, West Java, South Celebes, South Borneo. Secondly, 207 teachers were randomly selected from the same provinces. Using exploratory and confirmatory factor analyses revealed eight factors namely training benefit, instruction plan, process of active instruction, teacher professional satisfaction, media use, instruction evaluation, classroom situation, and school climate. This study concluded that all the factors were statistically valid and reliable, ready to be used for wider range of districts in this country.